women and ggirls in Hindi public sphere: Periodical literature in colonial North India - "Nijhawan, Shobna" (New Delhi, 2012)
he early 20th century in India witnessed the emergence of Hindi women's periodicals, which played a critical role in shaping a nationalist-feminist thought in India. Analysing the format and structure of Hindi women's periodicals, this volume investigates how women's periodicals became a medium for elite and middle-class women to think in new idioms and express themselves collectively in a period of social transition and political emancipation. In discussing topics surrounding domesticity, political emancipation, and language politics, the book argues that women's periodicals were an instigator of change and not merely a witness thereof. Providing case studies of Hindi women's periodicals including Stri Darpan (Women's Mirror), Grihalakshmi (Lakshmi of the Home), and Arya Mahila (Arya Woman), the volume also takes into account Hindi girls' periodicals like Kumari Darpan and Kanya Manoranjan, and looks at the nationalist demand for home rule for women.
Keywords: "Women in mass media, Women in Periodicals"